2022
DOI: 10.1038/s41598-022-19064-0
|View full text |Cite
|
Sign up to set email alerts
|

Cultivating epizoic diatoms provides insights into the evolution and ecology of both epibionts and hosts

Abstract: Our understanding of the importance of microbiomes on large aquatic animals—such as whales, sea turtles and manatees—has advanced considerably in recent years. The latest observations indicate that epibiotic diatom communities constitute diverse, polyphyletic, and compositionally stable assemblages that include both putatively obligate epizoic and generalist species. Here, we outline a successful approach to culture putatively obligate epizoic diatoms without their hosts. That some taxa can be cultured indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…The true grit method is novel in its procedural attempt to address concerns of contamination during marrow extraction. This procedure combines elements of previous forensic studies [7][8][9] and established diatom preparation protocols in phycology [10,11] to develop a method to extract diatoms from bone marrow that is time-efficient, minimizes contamination risk, and produces samples of intact diatoms from skeletal remains. The true grit method uses new and/or disposable materials to cut bone and extract the marrow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The true grit method is novel in its procedural attempt to address concerns of contamination during marrow extraction. This procedure combines elements of previous forensic studies [7][8][9] and established diatom preparation protocols in phycology [10,11] to develop a method to extract diatoms from bone marrow that is time-efficient, minimizes contamination risk, and produces samples of intact diatoms from skeletal remains. The true grit method uses new and/or disposable materials to cut bone and extract the marrow.…”
Section: Discussionmentioning
confidence: 99%
“…Referring to existing bone marrow digestion methods from forensics literature [7][8][9] and methods of diatom isolation in phycology [10,11], this research combines elements of various methods to create an extraction method that is time-efficient, minimizes contamination, and produces samples of intact diatoms. This version of diatom extraction from bone marrow is named the "True Grit Method," by which it will be referred to throughout the paper.…”
Section: Introductionmentioning
confidence: 99%
“…Diatoms are one of the most species‐rich eukaryotic algal groups, with an estimated 30,000–100,000 species (Mann & Vanormelingen, 2013). They can be found in many kinds of habitats: marine, freshwater, ice, terrestrial (soils, sand, mosses, rock walls) and can even be found as endosymbionts of dinoflagellates and epibionts of animals and macroalgae (Ashworth et al, 2022; Hehenberger et al, 2016; Mann & Vanormelingen, 2013; Round et al, 1990). The diatoms are also notable among the microalgae in their distinctive morphology; diatoms have a siliceous cell wall (the “frustule”), which can show high levels of morphological variability between taxa.…”
Section: Introductionmentioning
confidence: 99%